Super-hydrophilic nickel-based electrode with secondary array structure and preparation method of super-hydrophilic nickel-based electrode
By using femtosecond laser etching on the surface of the nickel felt, the problem of insufficient electrode design in the existing electrolytic hydrogen production technology is solved, and efficient electrolytic hydrogen production is achieved, reducing energy consumption and cost.
Patent Information
- Application Number
- CN202411994404.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
In the existing electrolytic water hydrogen production technology, insufficient electrode design leads to high energy consumption and high cost, and bubble growth and adhesion under high current conditions lead to an increase in mass transfer overvoltage, reducing electrolytic efficiency.
Femtosecond laser etching process is used to construct a micron-level secondary array structure on the primary surface of the nickel felt to form a ridge or square column array to improve the hydrophilicity and gas-emission of the electrode surface.
It significantly improves the wetting properties of the electrode surface and bubble desorption ability, reduces the mass transfer overpotential, and improves the energy efficiency of hydrogen production by electrolyzing water, which is suitable for industrial production.
Smart Images

Figure CN119776872A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a super-hydrophilic nickel-based electrode with a secondary array structure and a preparation method thereof. Background Art
[0002] Hydrogen energy has the advantages of high calorific value (143kJ / g) and zero carbon emissions of combustion products. Among them, green hydrogen technology produced by water electrolysis has broad application prospects. Traditional methods of hydrogen production by water electrolysis include: alkaline water electrolysis (ALK), proton membrane water electrolysis (PEM), anion membrane water electrolysis (AEM), and solid oxide electrolysis (SOEC). However, green hydrogen is currently still limited by industrial bottlenecks of high energy consumption and high cost. Therefore, how to achieve cost reduction and efficiency improvement of water electrolysis technology faces huge challenges.
[0003] In order to accelerate the reaction kinetics of water electrolysis, researchers in the industry have made great efforts in recent years to optimize the chemical composition and morphology of catalysts. However, the existing electrode design paradigm is still insufficient in achieving efficient mass transfer and improving overall catalytic performance.
[0004] The theoretical thermodynamic voltage for water electrolysis is 1.23 V, but in practice, due to ohmic loss, polarization loss, and mass transfer loss, a driving voltage of about 2.0 V is usually required, which reduces the energy efficiency. In addition to the high activity of the electrocatalyst, mass transfer at the catalytic electrode-electrolyte-gas (gas-liquid-solid) three-phase interface is also crucial to the overall performance. -2 ), due to the growth of a large number of bubbles and their attachment to the electrode, the mass transfer overvoltage deteriorates, the overall overvoltage rises, and the electrolysis efficiency is greatly reduced. Therefore, how to optimize the gas-liquid-solid three-phase interface in the water electrolysis reaction, improve the hydrophilicity of the electrode and accelerate the desorption of bubbles is crucial to improving the energy efficiency of high-current hydrogen production.
[0005] The wettability of the electrode surface has an important influence on the desorption of bubbles. The contact angle is an important parameter that characterizes the wettability of liquid to solid. The smaller the contact angle between the electrode surface and the electrolyte, the better the hydrophilicity, the faster the bubble desorption, and the mass transfer overpotential can be effectively reduced. Theoretical analysis of the Wenzel model and the Cassie-Baxter model shows that the surface roughness of the material will affect its hydrophilicity and hydrophobicity. Therefore, the constructed superhydrophilic surface should ensure that the electrolyte is in the Wenzel model state and reduce the contact area between the bubble and the catalytic electrode. The hydrophilicity and hydrophobicity of the electrode surface are related to the micro-nano structure and chemical composition of the electrode surface; in the technical scheme of Chinese patent application CN202211368749.2, superhydrophilicity is achieved by preparing a composite membrane material of a metal carrier layer, a sulfur-containing nickel plating layer, a hybrid Prussian blue layer and a hybrid hydrogel layer; but it needs to undergo electrodeposition, impregnation and heat treatment during the synthesis process, and the preparation steps are complicated. According to the records in the open literature (Apl Catal B: Environ, 2022, 317; 121786), Ren et al. constructed Ni-MoO2 / NF and NiMoO4 / NF, realizing super-hydrophilic super-gas transport structure, but the synthesis process used 150°C hydrothermal treatment and 420°C annealing treatment, the preparation process was complicated, and the structure was not stable enough and easy to fall off under high current operation conditions, which was difficult to meet the needs of industrial stable application. According to the records in the open literature (Chem Eng J, 2022.435; 134995.), Liu et al. used femtosecond laser to prepare a self-supporting electrode with a multi-level chestnut burr structure and grew CoO nanomaterials, but it could only obtain 10mA cm at a voltage of 1.51V. -2 The current density and electrochemical performance of the electrolyzer are far behind those of commercial water electrolysis equipment.
[0006] Given that there is still a lack of a method for preparing catalytic electrodes that is simple in process, low in cost, superior in performance and suitable for industrial production, in order to realize the industrial application of water electrolysis technology, it is urgent to develop a simple, fast and efficient method for preparing hydrophilic electrodes. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a super-hydrophilic nickel-based electrode with a secondary array structure and a preparation method thereof.
[0008] To solve the technical problem, the solution of the present invention is:
[0009] Provided is a super-hydrophilic nickel-based electrode with a secondary array structure. The nickel-based electrode uses a three-dimensional mesh nickel felt made of micron-sized pure nickel fibers as a substrate, and a micron-sized secondary array structure is periodically arranged on the primary surface of the nickel felt; the secondary array structure is any one or both of a ridge array or a square column array formed on the surface of the nickel felt by a femtosecond laser etching process.
[0010] As a preferred embodiment of the present invention, the dimensions of the ridge array are: ridge width a is 200-350 μm, ridge spacing b is 200-350 μm, and ridge height c is 60-100 μm.
[0011] As a preferred solution of the present invention, the dimensions of the square pillar array are: the side length a of the square pillar is 200-300 μm, the pillar spacing b is 200-300 μm, and the pillar height c is 50-80 μm.
[0012] As a preferred solution of the present invention, the secondary array structure is arranged on a single-side surface of the nickel felt.
[0013] The present invention further provides a method for preparing the aforementioned super-hydrophilic nickel-based electrode having a secondary array structure, comprising:
[0014] (1) preparing a three-dimensional mesh nickel felt from pure nickel fiber and using it as a substrate for further etching;
[0015] (2) According to the dimension data of the selected secondary array structure, the process parameters of femtosecond laser etching are set; then, etching operations are performed on the primary surface of one side of the nickel felt to remove part of the fibers on the surface according to a predetermined plan, and the remaining raised parts are presented as either or both of a periodically arranged ridge array or a square column array.
[0016] The present invention also provides an application method of the aforementioned super-hydrophilic nickel-based electrode with a secondary array structure, which is to use the nickel-based electrode as a working electrode to assemble a water electrolysis hydrogen production device.
[0017] Description of the invention principle:
[0018] Based on long-term research, the applicant has found that the micro-nano structure on the electrode surface is conducive to promoting the release of bubbles and avoiding the pinning of large bubbles on the electrode surface. On this basis, the present invention proposes a method for preparing a super-hydrophilic surface nickel-based electrode with a micron secondary array structure using a femtosecond laser in one step, so that the original anisotropic nickel felt surface obtains isotropic wettability after processing. A periodically arranged micron-sized secondary array structure is directly processed on the surface of the electrode base material by a femtosecond laser to improve the hydrophilicity and gas repellency of the electrode surface, optimize the three-phase interface of the electrode surface, and enhance its electrolytic performance; to solve the problems in the prior art that the preparation steps of hydrophilic electrodes are complicated, the cost is high, the electrochemical performance is poor, and it is not suitable for industrialization.
[0019] The reason why the micron-scale secondary array structure can bring super-hydrophilic and super-aerophobic properties to the nickel-based electrode is that the conditions for the formation of a super-wetting surface lie in the surface roughness structure and surface chemical composition. For the intrinsically hydrophobic nickel felt, arranging a secondary micron array on its primary surface will increase the roughness structure, increase the surface energy, and improve the hydrophilicity and aerophobicity of the material surface.
[0020] It has been verified that the original contact angle of the original nickel felt is 119.10°, and the actual contact angle of the droplet after being treated by the present invention reaches close to 0°. This indicates that the wettability of the electrode surface is greatly improved through the micron-level secondary array, which promotes the desorption of bubbles generated during the electrolysis process, ensures sufficient working area and provides stable three-phase active sites, is beneficial to the mass transfer process and charge and ion transfer during the electrolysis of water, accelerates the reaction kinetics of hydrogen production by electrolysis, and exhibits excellent electrolytic activity.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The method for preparing a super-hydrophilic interface nickel-based electrode with a micron secondary array structure provided by the present invention has simple preparation steps, super-hydrophilic and super-aerophobic properties, excellent electrochemical performance, low cost, and is very suitable for industrial production and application.
[0023] 2. Simple production steps: The construction of the secondary structure on the electrode surface can be processed in one step using a femtosecond laser. By adjusting the frequency, power, scanning rate and other parameters of the femtosecond laser, a periodic micrometer-scale array structure with a specific size can be obtained. No subsequent processing is required. The method is simple and easy to operate, and is suitable for scaling up to an industrial production scale.
[0024] 3. Optimize the wettability of the electrode surface: Through secondary structure design and femtosecond laser processing, the wettability of the electrode surface is greatly enhanced, and excellent hydrophilic and air-repellent properties are obtained. The actual contact angle between the electrode surface and the electrolyte can reach 0° (the original electrode contact angle is 119.10°), which is beneficial to the transmission of water and the desorption of bubbles during the electrolysis process.
[0025] 4. Improve the electrochemical performance of hydrogen production electrodes: The prepared super-hydrophilic interface nickel-based electrode with a micron secondary array structure exhibits excellent electrolytic hydrogen production activity, greatly reducing the mass transfer barrier during the electrolysis process (especially under industrial high current density), reducing the overpotential of hydrogen evolution, and improving energy efficiency. It has promoted the development of green hydrogen cost reduction and efficiency improvement.
[0026] 5. Reduce the use of precious metal catalysts: The prepared super-hydrophilic interface nickel-based electrode with a micron-level array structure can be used as a collection of catalysts and gas diffusion layers, without the need for catalyst loading, and has good electrochemical performance and stability during electrolysis of hydrogen. In addition, the electrode can also be used as a cathode and anode electrode at the same time, avoiding the use of precious metal elements such as Pt and Ir, and without the participation of binary or ternary metals, reducing the cost and manufacturing difficulty of electrolytic hydrogen production electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagrams of the structures of the ridge array (left figure) and the square column array structure (right figure) on the surface of the nickel-based electrode of the present invention.
[0028] Figure 2 This is a scanning electron microscope image of the hydrophilic micro-nano interface of the nickel-based electrode of the present invention, with a magnification of 35.
[0029] Figure 3 This is a scanning electron microscope image of the hydrophilic micro-nano interface of the nickel-based electrode of the present invention, with a magnification of 100.
[0030] Figure 4 This is a comparative surface contact angle test.
[0031] Figure 5 Static contact angle test of nickel-based electrode microstructure surface.
[0032] Figure 6 This is a simulation of the dynamic wetting angle of Example 1 of the present invention.
[0033] Figure 7 HER electrochemical performance curves of different examples in the present invention. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0035] 1. The super-hydrophilic nickel-based electrode with a secondary array structure provided by the present invention is a three-dimensional mesh nickel felt made of micron-sized pure nickel fibers as a substrate, and a micron-sized secondary array structure is periodically arranged on the primary surface of the nickel felt; the secondary array structure is any one or both of a ridge array or a square column array formed on the surface of the nickel felt by a femtosecond laser etching process (such as Figure 1As shown). As an optional solution, the size specifications of the ridge array are: ridge width a is 200-350μm, ridge spacing b is 200-350μm, and ridge height c is 60-100μm. The size specifications of the square column array are: square column side length a is 200-300μm, column spacing b is 200-300μm, and column height c is 50-80μm. Since the electrolyte flow is arranged only on one side of the catalytic electrode, the secondary array structure is arranged on the single-side surface of the nickel felt, which is efficient, simple and low-cost to process.
[0036] 2. The preparation method of the above-mentioned super-hydrophilic nickel-based electrode comprises the following steps:
[0037] (1) preparing a three-dimensional mesh nickel felt from pure nickel fiber and using it as a substrate for further etching;
[0038] (2) According to the dimension data of the selected secondary array structure, the process parameters of femtosecond laser etching are set; then, etching operations are performed on the primary surface of one side of the nickel felt to remove part of the fibers on the surface according to a predetermined plan, and the remaining raised parts are presented as either or both of a periodically arranged ridge array or a square column array.
[0039] When designing the size of the micron secondary array structure, on the one hand, it is necessary to consider the improvement of the wettability of the electrode surface, and on the other hand, it is necessary to consider the processing limit and difficulty of the femtosecond laser. When the selected secondary structure processing size is too large, the surface roughness value of the prepared micron structure is small, and the hydrophilicity of the nickel felt is not significantly improved; when the selected secondary structure processing size is too small, it will exceed the processing capacity of the femtosecond laser and waste processing time.
[0040] 3. The application method of the super-hydrophilic nickel-based electrode is to use the nickel-based electrode as a working electrode to assemble a water electrolysis hydrogen production device.
[0041] 4. The present invention is further described in detail below through specific embodiments.
[0042] (1) First, the nickel wire is drawn into fibers by a bundle method, then air-formed into a mesh, and finally sintered into a fiber felt. The preparation technology of the bundle drawing method adopted can produce nickel fibers with different wire diameters of 6 to 40 μm to meet the requirements of nickel fiber felts with different performances; the nickel fiber is laid into a mesh by an air-form method. By adjusting various process parameters, the laid nickel fiber mesh has good uniformity and is free of defects such as bundled fibers and fiber agglomeration.
[0043] Compared with pure nickel, nickel felt has a good three-dimensional mesh porous structure, and therefore has the advantages of high porosity, large specific surface area, uniform pore size distribution, and strong corrosion resistance, and performs well in water electrolysis reactions.
[0044] (2) Cut into multiple pieces of 1×1 cm2 The nickel felt is then scanned and processed on the surface of the nickel felt using a femtosecond laser process. Etching operations are performed on the surfaces of both sides of the nickel felt respectively. Part of the fibers on the surface are removed according to a predetermined plan. The remaining protrusions are presented as either or both of a periodically arranged ridge array or a square column array. The structural schematic diagrams of the two are shown in FIG. Figure 1 shown.
[0045] During femtosecond laser processing, the control parameters are: power 4w, speed 1000mm / s, frequency 300k. The processing dimensions of the secondary array structure in each embodiment are as follows:
[0046] Example 1 A secondary square pillar array rough structure is processed by femtosecond laser, wherein the side length of the square pillar is a=300 μm, the spacing is b=200 μm, and the height is c=50 μm;
[0047] Example 2: A secondary square pillar array rough structure is processed by femtosecond laser, wherein the side length of the square pillar is a=200 μm, the spacing is b=250 μm, and the height is c=80 μm;
[0048] In Example 3, a secondary groove array rough structure is processed by femtosecond laser, wherein the ridge width a=200 μm, the ridge spacing b=200 μm, and the ridge height c=60 μm;
[0049] In Example 4, a secondary groove array rough structure is processed by femtosecond laser, wherein the ridge width a=200 μm, the ridge spacing b=350 μm, and the ridge height c=60 μm.
[0050] Comparative Example 1 is a raw nickel felt without any processing.
[0051] Examples 1 to 4 are marked as S1, S2, S3, and S4, respectively, and Comparative Example 1 is marked as S0. The processing parameters of each group are shown in Table 1.
[0052] Table 1 Processing data of various embodiments of the present invention
[0053] Group structure Processing size (a*b*c) / μm S0 Unprocessed none S1 Square Column 300*200*50 S2 Square Column 200*250*80 S3 Ridge 200*200*60 S4 Ridge 200*350*60
[0054] Figure 2 and Figure 3 The scanning electron microscope images of Examples 1 to 4 at magnifications of 35 and 100 respectively show that the processed substrate surface exhibits obvious rough ridges and square column structures (marked by white dotted lines in the figure).
[0055]
Contact angle test
[0056] The contact angle is a measurement method for determining the interaction between solid and liquid interfaces and is an important parameter for measuring the wetting properties of liquids on materials. The specific operation is to place a droplet on the surface of a solid sample, use a microscope and a camera to obtain an image of the droplet shape, and then use digital image processing and multiple algorithms to calculate the wetting angle of the droplet in the image.
[0057] Figure 4 This is the contact angle measurement result of S0. Based on the image analysis method, the average value of its intrinsic contact angle is measured to be 119.10°, indicating that the hydrophilicity of the original flat nickel felt is poor and it is not suitable for gas desorption. Figure 5 The contact angle measurement results of S1~S4 are shown in Figure 2. Their actual contact angles all reach 0°, indicating that the micrometer secondary array structure design greatly enhances the wettability of the hydrogen evolution electrode surface and obtains super hydrophilic and super aerophobic properties. In addition, COMSOL Multiphysics was used to perform numerical simulation on the dynamic wettability of the S3 surface. The results are shown in Figure 2. Figure 6 When the droplet fell onto the nickel felt surface, complete wetting quickly occurred, indicating that the constructed superhydrophilic electrode surface has excellent dynamic wetting properties.
[0058]
Electrochemical performance evaluation
[0059] The electrochemical measurement adopts a three-electrode system, with the processed sample as the working electrode, the counter electrode as a graphite rod, and the reference electrode as a saturated Hg / HgO electrode. During the test, the Hg / HgO electrode is converted to a standard hydrogen electrode RHE. The electrolyte is 1.0MKOH, the electrolyzer temperature is set to 65°C, and the LSV test of HER and OER is carried out in a single electrolyzer. The test range is 0 to -0.8Vvs.RHE, and the scan rate is 10mV / s.
[0060] The HER electrochemical performance curves under the stirring speed of 60 rpm and the stirring speed of 500 rpm are shown as follows: Figure 7 As shown in a (left) and b (right). At any potential, the hydrogen evolution current density of the nickel felt (S1-S4) with a micrometer secondary array structure is greater than that of the untreated (S0), indicating that the desorption capacity of bubbles and the mass transfer capacity during the electrochemical reaction are significantly increased through the construction of the secondary structure. In addition, the convection introduced by the external force significantly optimizes the mass transfer of the original S0, while it has no significant effect on the mass transfer of the processed material, proving that the prepared material itself has good hydrophilicity and mass transfer capacity.
[0061] In summary, the super-hydrophilic interface nickel-based electrode with a micron secondary array structure provided by the present invention can significantly improve the wettability of the interface, accelerate the desorption of bubbles during electrolysis, reduce mass transfer overpotential, and optimize energy efficiency by preparing a rough structure of micron-scale grooves or square pillar arrays on the three-dimensional mesh primary surface of the nickel felt substrate.
[0062] The preparation method of the present invention has simple procedures and the prepared super-hydrophilic electrode has excellent performance. The fine micron structure is prepared by femtosecond laser processing, which has the advantages of simple operation, one-step completion, fine control, and large-area operation. By controlling parameters such as femtosecond laser power and scanning speed, a super-hydrophilic electrode with a micron secondary array structure with stable structure and excellent performance can be obtained.
Claims
1. A super-hydrophilic nickel-based electrode with a two-level array structure, characterized in that: The nickel-based electrode is based on a three-dimensional mesh nickel felt made of micron-sized pure nickel fibers, and a micron-sized secondary array structure is periodically arranged on the primary surface of the nickel felt. The secondary array structure is any one or both of a ridge array or a square column array formed on the surface of the nickel felt by using a femtosecond laser etching process.
2. The super hydrophilic nickel-based electrode according to claim 1, characterized in that: The dimensions of the ridge array are: ridge width a is 200-350 μm, ridge spacing b is 200-350 μm, and ridge height c is 60-100 μm.
3. The super hydrophilic nickel-based electrode according to claim 1, characterized in that: The dimensions of the square column array are: the side length a of the square column is 200-300 μm, the column spacing b is 200-300 μm, and the column height c is 50-80 μm.
4. The super hydrophilic nickel-based electrode according to claim 1, characterized in that: The secondary array structure is arranged on a single-side surface of the nickel felt.
5. The method for preparing the super-hydrophilic nickel-based electrode with a two-level array structure as described in claim 1, characterized in that: include: (1) preparing a three-dimensional mesh nickel felt from pure nickel fiber and using it as a substrate for further etching; (2) According to the dimension data of the selected secondary array structure, the process parameters of femtosecond laser etching are set; then, etching operations are performed on the primary surface of one side of the nickel felt to remove part of the fibers on the surface according to a predetermined plan, and the remaining raised parts are presented as either or both of a periodically arranged ridge array or a square column array.
6. The method according to claim 5, characterized in that The dimensions of the ridge array are: ridge width a is 200-350 μm, ridge spacing b is 200-350 μm, and ridge height c is 60-100 μm.
7. The method according to claim 5, characterized in that The dimensions of the square column array are: the side length a of the square column is 200-300 μm, the column spacing b is 200-300 μm, and the column height c is 50-80 μm.
8. The method for applying the super-hydrophilic nickel-based electrode with a secondary array structure as described in any one of claims 1 to 4, characterized in that: The nickel-based electrode is used as a working electrode to assemble a water electrolysis hydrogen production device.
Citation Information
Patent Citations
Superhydrophilic nickel-based multilayer composite membrane materials, their preparation methods and applications
CN115430597B
Cited By
Preparation method of efficient mass transfer anti-precipitation sea water hydrogen production electrode constructed by femtosecond laser
CN121976217A
Hydrogen evolution electrode preparation method based on femtosecond laser liquid phase processing
CN121976241A